(untitled) (INNOTEC, 2022)
Honey is a complex food that bees make from nectar and honeydew, incorporating their own substances. Its composition varies according to floral origin, area and weather conditions. The protected area Estero de Farrapos in Uruguay has natural conditions that attract beekeepers to produce honey, which they sell in bulk. Characterizing these honeys and differentiating them by geographical and botanical origin constitutes an opportunity for commercial valorization. Thirty samples of honeys from apiaries from this region were studied, evaluating physicochemical characteristics (color, humidity, hydroxymethylfurfural, electrical conductivity, free acidity, pH) and melisopalynological characteristics. The results for humidity (17.3%), Hydroxymethylfurfural (6.16 mg/Kg) and free acidity (30.2 meq/Kg) allow to confirm its bromatological quality and the use of good handling practices in production and processing processes extraction. The parameters color (90.5 mm Pfund) and electrical conductivity (0.5854 mS/cm) could be used to characterize these honeys, helping to differentiate them by botanical and geographical origin. The honeys studied have a high pollen richness with the pollen spectra that allow them to be associated with the production region. Many turned out to be monoflorals of the native species Scutia buxifolia and Blepharocalyx salicifolius and several are very close to being so. An adequate production protocol could optimize this characteristic to its full potential.